Evaluation of a TX-chain for Cognitive Radio Applications - Mattsson, Anders; Strömberg, Simon (My University, 2013)
Today, the frequency spectrum up to the GHz range is more or less completely allocated. However, the allocated spectrum is to a large extent underutilized. Cognitive radio is a new emerging wireless technology that aims to increase the utilization efficiency of the radio spectrum. The task consisted of the evaluation of a TX-chain for an RF-ASIC intended for cognitive radio applications. More specifically, the TX-chain is implemented in a transceiver for the control channel used in the cognitive radio system. The system has to be configurable for different transmission frequencies. The aim was to propose a design that is optimized for low power consumption and small chip area. A pre-study was conducted where the separate blocks in the TX-chain were investigated in order to arrive at a system design, which was then modelled in Matlab. The simulation results were evaluated mainly in terms of spectrum mask compliance but also modulation accuracy. The proposed design implements GFSK modulation according to the Bluetooth standard, transmit- ting at frequency bands 470-790MHz, 2.400-2.483 GHz, and 2.900-3.100 GHz. The design implements a harmonic rejection mixer, which relaxes the filter demands of the design. In terms of chip area and power efficiency, the results strongly suggest that the proposed design has an advantage compared to a more conventional design. The suggested TX-chain complies with the spectrum masks in each band as well as the out-of-band regulations. However, all the specifications set regarding the modulation accuracy could not be met. The mixer phase mismatch of 2 ◦ will have to be re-evaluated to 1 ◦ error, which will increase the complexity of the layout.
Keywords: Data- och informationsvetenskap; Computer and Information Science